Comparative analysis of pricing decisions made by listed companies representing different industry sectors: evidence from Sri Lanka - Indrani, M.W.; Naidoo, M.; Wickremasinghe, G. (Faculty of Management Studies & Commerce, University of Jaffna, 2020)
Pricing a product is one of the most important aspects of the decision-making process of a business. This study explores pricing methods applied and, specific surroundings and influences/ bases that individual companies exercise in making certain pricing decisions. Applying the Mixed Method Research approach, data were collected mainly through in-depth interviews and discussions further to a face-to-face questionnaire survey made with senior management/ finance executives of companies. Facilitating with SPSS software quantitative data were analyzed using frequency tables and Fisher's exact test, and thematic analysis and content analysis were applied for qualitative data. Findings depict different settings that individual companies are in operation thereby providing specific bases for their pricing decisions. Thus, considerable variations appear among individual companies/sectors in making pricing decisions that are determined by different features specific to the business and sometimes to the sector i.e. plantation sector. Through such pricing decisions, companies decisively expect to maximize profit and also a concern for maximizing sales and increasing market share. This study concludes that it is more sensible to take pricing decisions by analyzing specific structures of the products, markets and of the business/ sector; such as types/ status of products and level of diversification, nature of markets served and competitive position, nature of target customers/ buyers, explicit settings i.e. plantation sector and specific agreements made with buyers or any associated parties i.e. subsidiaries and Head office. These findings provide insights to businesses operating in diverse surroundings, in evaluating alternative pricing strategies and in making pricing decisions towards achieving their objectives and hence the survival of the business.
Keywords: Industry sectors; Listed companies; Pricing decisions; Pricing methods; Specific surroundings